PEMILIHAN MODEL REGRESI LINIER MULTILEVEL TERBAIK - Bertho Tantular; . Aunuddin; Hari Wijayanto (FORUM STATISTIKA DAN KOMPUTASI, 2009)
Linear regression models is used to describe relationship between dependent variable and independent variables. In a survey research, data was used often have hierarchical structure or nested structure. In this research, independent variables can be defined at any level of the hierarchy but dependent variable can only be defined at the lowest level of the hierarchy. Multilevel regression models is one of the methods can be used to analyze this data. Some authors purpose many models can be used to analyze data with hierarchical structures. Deviance as -2 log likelihood was defined as the measure goodness of fit. The difference of the deviance for two nested models was a method for comparing that two models.